Elaboración de accesorios metálicos para el hogar reutilizando los desechos de los talleres de metalmecánica de la parroquia San Buenaventura - Mazón Sumi, Klever Fabricio (2017)
This research project was carried out in the parish of San Buenaventura in Latacunga city, where 24 metalmecánica are located, which are dedicated to metalworking in which it can be verified that they generate metallic wastes and these are only used as recycling wastes for Subsequently go to the steelmaking process, therefore in this activity shows that the wastes generated are not being used properly which in turn cause pollution and many of these elements considered as scrap can be used for other processes such as making recycled accessories. From this and through the interviews with the owners of the industries researchers realized that it must work to minimize the impacts generated by these activities with this research proposes to use the methodology of the ecological circle of the three R to reuse the waste (scrap) Generated by the metalworks of San Buenaventura for the elaboration of metallic accessories, in their classification during a month average data, it is estimated to collect 3136 kg of waste taking into account maximum and minimum data in the same way that every month is going to observe varied results of the 24 metalmecánicas and industries, in what we have proposed to reuse, a total of 157 kg being a sample for the project to be executed, through this proposal and the operation of the same could be made 26 accessories of different models and based on the survey accessories have been developed for room, kitchen and gardening, this could be done during 9 days giving as result that this operation can be repeated three times during the month, doing this operation during the month can be reused an amount of 471 kg being this our installed capacity of the metalmecánica, one of the main objectives is to reduce environmental pollution, it is so in its elaboration it was possible to verify the optimization of this resource generating a minimum waste of 4%, being used 96%. At the time of the economic study it was obtained a positive return on investment, it could also predict the social impact in which people are involved buying our products and thus be part of a medium based on recycling. In addition, to generating environmental impacts positive solutions that would help the planet reduce unnecessary energy sources while helping to minimize environmental impact.